Social Data Analytics sebagai Metode Alternatif dalam Riset Psikologi - Cleoputri Yusainy; Anif Fatma Chawa; Siti Kholifah (Faculty of Psychology Universitas Gadjah Mada, 2017)
The usage of technologically based utilities has been increasing rapidly in our daily life. This phenomenon breeds two fundamental changes: Data explosion and social structures. It takes a different approach to gain insights and benefits from the phenomenon. In psychological science, the acquaintance of alternative methods to keep up with the problems should be a necessity. This article introduces two social media data analytical techniques, namely (i) sentiment analysis as the process of computationally identifying, extracting, and quantifying the effective condition towards a particular target, and (ii) social network analysis (SNA) as the process of investigating social structures through the use of Graph Theory dan Network Science. Overviews are presented in general terms with the expectation to bring the quality of research in Psychology to the next level.